Analysis of the Relationship between Pulmonary Hypertension and Tuberculosis Patients at RS Ibnu Sina Makassar January - June 2023 - Alfian, Dwi Hermin; Wiriansya, Edward Pandu; Ardiyanto, Ardiyanto; Arif, Muhammad; Anggita, Dwi; Ginayah, Mir’atul (PT FORMOSA CENDEKIA GLOBAL, 2024)
Pulmonary hypertension (PAH), seen in 20%-40% of chronic respiratory diseases, is linked to the severity of these conditions. Tuberculosis, a bacterial infection causing lung damage and impaired function, can contribute to this increased blood pressure in the pulmonary arteries, complicating patient outcomes by worsening both conditions. This study used an analytical observational method with a cross-sectional approach, measuring independent and dependent variables simultaneously at a single point in time. It focused on analyzing the relationship between pulmonary hypertension and pulmonary tuberculosis in patients. The study found that most respondents were aged 51-70 years, with no significant link between age or gender and hypertension (P-values=0.091 and 0.655, respectively). Light smoking was significantly associated with hypertension (P-value=0.001), while nutritional status was not (P-value=0.332). Significant relationships were found between blood pressure (P-value=0.002) and spirometry results (P-value=0.000) with hypertension. Thus, blood pressure, smoking habits, and spirometry results were key factors influencing pulmonary hypertension in the 60 patients studied. There is a significant relationship between Pulmonary Hypertension and Tuberculosis patients at Ibnu Sina Hospital, Makassar, January - June 2023.